Transformation learning among persons with cardiac problems to achieve a balance of occupation. - Dubouloz C; Chevrier J; Savoie-Zajc L (Canadian Journal of Occupational Therapy, 2001)
Transformative learning is a process of adaptation that allows for profound personal change in occupational therapy clients. This process is provoked by a triggering factor, such as illness, which results in a critical reflection on values, beliefs, feelings and personal knowledge associated with the object of change (Mezirow, 1991). As part of an objective aimed at modifying the balance of occupation, nine participants were interviewed over a 6 month period to explore their processes of change. Eight concepts related to the objective of change of the balance of occupation emerged from an inductive data analysis process (Glaser and Strauss, 1967). The perception of work was interpreted by the authors as having undergone the most significant sense of transformation amongst the participants. Two other perceptions, 1) the definition of self and 2) the concept of health emerged as new elements essential to the modification of the balance of occupation. The transformation process linked to these eight concepts revealed a specific structure and sequence. The results highlight the primary role of critical reflection amongst occupational therapy clients and underline the importance of deconstructing common values and beliefs which could slow down the process of change. Moreover, the development of new values and beliefs is a vehicle for change in occupational therapy.